Determinación de hdl-colesterol y ldl-colesterol sérico en personas adultas de ambos sexos que acuden al Centro de Salud de Víctor Larco, del distrito de Víctor Larco Herrera, junio del 2009 - Vidal Sobrado, Karin Eugenia (2009)
It developed the research Type I: "Determination of HDL-cholesterol and serum LDL-cholesterol in adults of both sexes attending the health center Victor Larco, District Victor Larco Herrera, June 2009," using the precipitating reagent method for HDL-C and LDL-c, for it worked with 96 adults of which were applied informed consent and a survey, then proceeded to making 3mL blood sample, processing the same , leading to reading the spectrophotometer at 505 nm, calculating data, and these were: 10.42% of patients have elevated LDL-c, with 70% women and 30% men, also the results for HDL, were: 47.92% persons with low risk (> 60mg/dL), 39.58% at moderate risk (40-60mg/dL) and 12.5% high risk (<40 mg / dL); included in the latter 75% female in the range of 63años age 54-and 25% men between 45 and 72 years